Namādhiju Ta’līmi al-Lughah al-‘Arabiyah ‘alā Ḍaw’i al-Dhakā’āt al-Muta’addidah Lada al-Ṯalabah al-Mawhūbīn fī Madrasah Malik Ibrāhīm al-Mutawassiṯah Bikirsīk - Saiul Anah; Yusuf Arisandi (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
There are three objectives of this research: 1) to identify the the multiple intelligences learning models of Arabic learning for Smart and Gifted students at Malik Ibrahim Junior High School of Gresik and Amanatul Ummah Junior High School of Mojokerto, 2) to analyze the techniques of multiple intelligences learning models of Arabic learning for Smart and Gifted students at Malik Ibrahim Junior High School of Gresik and Amanatul Ummah Junior High School of Mojokerto, and 3) to describe the benefits of Multiple Intelligences in learning Arabic for Smart and Gifted students at Malik Ibrahim Junior High School of Gresik and Amanatul Ummah Junior High School of Mojokerto. The researcher applied a qualitative approach namely case study method. The data was taken from recording observation and interview and was analyzed by using interactive model analysis. The substantive findings from this study were: (a) the multiple intelligences learning models of arabic learning for smart and gifted student at Malik Ibrahim Junior High School of Gresik and Amanatul Ummah Junior High School of Mojokerto were multiple model and interdisiplinary towards the development of learning activities. 2) The techniques of Multiple Intelligences in learning Arabic were: a) Question and Answer technique. There were two varieties of discussion: closing question (a-one-possible-answer question) and opening question(a-many-possible-answer question). b). Speech Tehnique. Speech tehnique is weekly interdisiplinary learning activity which requires the student to deliver a speech with a theme based on their arabic book. c). Discussion Tehnique 3) Multiple Intelligences had some benefits for every learning model; there were motivation, customisation learning and easy for learning activity. The formal research findings showed that multiple-intelligence learning model brings impacts on the students’ motivation dan characters based on their intelligence. Keywords: learning models, multiple intelligences, gifted students